ANALISIS PENERAPAN BIAYA SISA BAHAN, PRODUK RUSAK, DAN PENGERJAAN KEMBALI DALAM PROSES PRODUKSI PADA UMKM “SEMASA THAI TEA” DI KABUPATEN BEKASI - Purwanti; Elyzafah, Beby Berlian; Arrofi , Maedina Wilda; Tina, Titha Egis; Pratiwi, Zahra Eka; Gunawan, Yudha Febrian; Umayah, Genta Anas; Veriyanto, Andhika Rahman; Navita, Cahya; Krisnani, Novia Dwi; Syahroni, M. Kamil; Adriena, Nurul Azmi (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
MSMEs (Micro, Small, and Medium Enterprises) refer to economic activities owned by individuals or business entities that meet specific criteria as outlined in Law Number 20 of 2008. As a vital component of the national economy, MSMEs play a crucial role in supporting economic growth. However, in their daily operations, MSMEs often face challenges in managing production costs, particularly those related to leftover materials, defective products, and rework. This study aims to investigate the application of cost accounting for leftover materials and defective products in the MSME Thai Tea, located in Bekasi Regency. The research adopts a qualitative descriptive approach, with data collected through in-depth interviews with the owner of the MSME. The findings reveal that cost recording for leftover materials and defective products is still conducted irregularly. Leftover materials are generally overlooked in production efficiency evaluations, and rework costs are not separated from the main production costs. This situation results in a lack of optimal information for managerial decision-making. The study recommends the implementation of a simple yet structured cost accounting system to help MSMEs more accurately identify cost elements and improve production efficiency. These findings are expected to contribute to the development of cost accounting literature in the MSME sector and serve as a practical guideline for business owners in managing production costs effectively